Improving drainage water quality: Constructed wetlands-performance assessment using multivariate and cost analysis. Issue 2 (1st October 2018) - El Hawary, A.; Shaban, M.
Abstract: Multivariate analysis of variance followed by multiple comparisons and discriminant function analysis were used to characterize the performance of three plant species ( water hyacinth WH, reed RD and duckweed DW ) to remove drainage water pollutants using constructed wetlands under the Egyptian conditions. In addition, a simple economic comparison that covers the basic expenses were carried out. During the period from January 2016 to December 2017, input and output water for each treatment cell was monthly sampled and analyzed for five parameters namely; Total Suspended Solids, Dissolved Oxygen, Biochemical Oxygen Demand, Ammonia-N and Phosphate. The results showed wide variation in the removal efficiency of the tested plants according to the monitored pollutants. The efficiencies for DW and WH decrease during the winter season. In the meantime, RD efficiency improves during summer. The cost estimation revealed that the average annual plantation, harvesting and disposal costs estimated for the DW, WH and RD were 6.17, 6.17 and 1.25 per cubic meter, respectively. Consequently, RD plants are recommended as a first priority for treating polluted drainage water.